Wasiat Wajibah Kategori Ahli Waris Pengganti Dalam Hukum Waris Di Indonesia - Basit Misbachul Fitri, Abdul; Fadhilatur Rofiah, Ayu (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2021)
A mandatory will is a will whose implementation is not influenced or does not depend on the will or will of the deceased and must be implemented. The provisions of the mandatory will is the result of the ijtihad of the scholars in interpreting verse 180 of surah al-Baqarah. Some Uama' allow it and some forbid it. Based on the hadith about the will, the hadith from Thabit Ibn Anas that the Prophet SAW said: to Abu Talhah, "Make it for your poor and relatives", then Abu Talha gave it to Hassan and Ubay Ibn Ka'b. Rasulullah SAW, limited the will as far as possible it is not obligatory. If the heirs are rich, then shadaqah is recommended to be different from the settlement of debts and zakat. If seen from the Fiqh Perspective, Maliki Ulama: wills must be addressed to people who have dependents on debt or deposited goods. Hanafiyah Scholars: A will that must be carried out due to the relationship of rights with the owner of the sample right to return the deposited goods and debts whose documents are not known. Syafiiyah scholars: will law is divided into three types, it is not permissible, it is permissible or not obligatory and the law is debated about its obligations. In a formal juridical perspective, as in civil law, article 209 of mandatory will, when compared between KHI and BW, there are similarities and the difference lies in the successor heirs. The equation is that the replacement part of the heirs is not greater than the part of the heirs being replaced. preferably grandchildren from male descendants, this is the implication of a patrilineal Arab culture based on responsibility in earning a living. In BW, because there is no difference between men and women in terms of inheritance, either from male or female offspring with a bilateral parental family system.